Phylogenetic positions of the rotifer Brachionus plicatilis species complex from Indonesian waters - Stenly Wullur; Petrus P Letsoin; Inneke F M Rumengan (Depik, 2024)
The Brachionus plicatilis species complex comprises a group of rotifers commonly found in marine and brackish water environments worldwide. This group has garnered substantial attention due to its ecological significance and its utility in aquaculture research. Notably, the B. plicatilis sp. complex is renowned for its remarkable genetic diversity, which has been extensively investigated through molecular and taxonomic studies. Various genetic markers, including ribosomal DNA and mitochondrial DNA, have been employed to identify several distinct genetic lineages within the B. plicatilis sp. complex. Understanding the taxonomy and phylogenetic relationships within the B. plicatilis sp. complex holds significant implications for its application in aquaculture and ecotoxicology research. In this study, we conducted an analysis of the mitochondrial DNA cytochrome c oxidase subunit I (COI) gene using a dataset of 305 sequences, including four Indonesian rotifers belonging to the B. plicatilis sp. complex. These rotifers were obtained from Sulawesi Island (MNBO and MNSL), Bali Island (AY785226), and Sumatra Island (LMPG). Our primary objective was to determine their phylogenetic positions relative to molecular data available in the GenBank database. We calculated genetic distances among these rotifers using the Tamura Nei model. The results of Maximum Likelihood tree analyses revealed distinct clustering patterns among the Indonesian rotifers. Those originating from Sulawesi Island (MNBO and MNSL) and Bali Island (AY785226) formed the SS1 group (B. ratundiformis), whereas those from Sumatra Island (LMPG) comprised the SM2 group (B. koreanus). This study underscores the importance of molecular phylogenetic analysis in advancing our comprehension of the diversity and evolutionary relationships within the B. plicatilis sp. Complex.Keywords:PhylogenyRotiferaBrachionus plicatilisSpecies complexIndonesia